2022
DOI: 10.3390/ani12192519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Canine-Obtained Lactic-Acid Bacteria on the Fecal Microbiota and Inflammatory Markers in Dogs Receiving Non-Steroidal Anti-Inflammatory Treatment

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) may cause enteropathy in dogs and probiotics may be one option to prevent this. The objective of this study was to determine whether the administration of canine-obtained lactic acid bacteria (LAB) has an effect on the frequency of diarrhea, the composition of the fecal microbiota, and/or markers of gastrointestinal inflammation in dogs receiving NSAIDs when compared to dogs given NSAIDs and a placebo. A total of 22 dogs treated with NSAIDs for various clinical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
9
2
Order By: Relevance
“…36 Another recent study that evaluated dogs receiving an NSAID with and without a probiotic found that probiotic administration did not have an effect on the fecal CMDI or fecal calprotectin concentrations. 31 Probiotic administration in dogs with chronic diarrhea can have beneficial effects, including upregulation of tight junction protein expression and normalization of dysbiosis, our results did not show a benefit of probiotic administration in dogs administrated PPI as measured by the fecal CMDI. 19,20 Calprotectin is a protein complex found primarily in neutrophils and is used as a marker of intestinal inflammation in people.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…36 Another recent study that evaluated dogs receiving an NSAID with and without a probiotic found that probiotic administration did not have an effect on the fecal CMDI or fecal calprotectin concentrations. 31 Probiotic administration in dogs with chronic diarrhea can have beneficial effects, including upregulation of tight junction protein expression and normalization of dysbiosis, our results did not show a benefit of probiotic administration in dogs administrated PPI as measured by the fecal CMDI. 19,20 Calprotectin is a protein complex found primarily in neutrophils and is used as a marker of intestinal inflammation in people.…”
Section: Discussioncontrasting
confidence: 71%
“…There was no difference in the fecal CMDI of dogs undergoing hemilaminectomy that received intra‐operative antibiotics with or without probiotic (Visbiome) 36 . Another recent study that evaluated dogs receiving an NSAID with and without a probiotic found that probiotic administration did not have an effect on the fecal CMDI or fecal calprotectin concentrations 31 . Probiotic administration in dogs with chronic diarrhea can have beneficial effects, including upregulation of tight junction protein expression and normalization of dysbiosis, our results did not show a benefit of probiotic administration in dogs administrated PPI as measured by the fecal CMDI 19,20 …”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Although our data suggested that probiotics improved health in mice, we next investigated whether probiotics affect the gut microbiota that may regulate host health. Canine-derived probiotics have been reported to have many beneficial effects on the gastrointestinal microbiomes and immune systems of a variety of species ( O’Mahony et al, 2009 ; Herstad et al, 2022 ). The richness, Chao1, Shannon, Simpson, PD whole tree, and ACE indices were used to assess species richness and diversity.…”
Section: Discussionmentioning
confidence: 99%